Users and Contexts of Use of Romanian Multilingual Dictionaries - Mocanu, Mihaela; Bursuc, Alina-Mihaela (Lexikos, 2020)
A significant number of multilingual dictionaries (in at least three languages) were published in Romania after the Revolution of December 1989. In the context of an unprecedented evolution of multilingualism, experts in various fields, as well as higher education professors identify specific communication needs and potential users and foresee preferential contexts of dictionary use. This article presents the outcomes of a study on the main categories of users and contexts of use of multilingual dictionaries edited in Romania after 1989. This analytical approach targets a representative sample of dictionaries selected on the basis of three criteria imposed by the research limits: temporal (dictionaries edited in the period 1990–2010), idiomatic (works presenting the list of entries in Romanian) and formal (the multilingual character stated explicitly in the title of the dictionary). The first part of the article accounts for the stage of research related to dictionary users and a short presentation of Romanian lexicography in general and of multilingual lexicography in particular. The second part of the study describes the methodology and proposes a systematization of the categories of potential users and the contexts of dictionary use as envisaged by the authors of the dictionaries under analysis.